The Effect of Soft Drink Consumption on PH in Stimulated and Unstimulated Saliva : Quasi Experimental with Post-Test Only Comparison Group - Fitri Dona Siregar; Vandersun Lestari; Stevi Nencia Purba (Journal Research of Social Science, Economics, and Management, 2025)
Consuming soda will lower the pH of saliva due to its acid content. This decrease in pH can affect the balance of the oral cavity. Stimulated saliva will have a better buffering capacity than unstimulated saliva. The purpose of this study was to determine the effect of soda consumption on the pH of stimulated and unstimulated saliva. This was a quasi-experimental study with a post-test only comparison group. The study population was 166 male and female students of the Dentistry Department at Prima Indonesia University. The sample size was 68 students, divided into two groups: stimulated and unstimulated saliva. The pH was measured using a digital pH meter. Data were analyzed using the Mann-Whitney test. The results showed that the average pH after soda consumption in the stimulated saliva group was 8.03 ± 0.129 and in the unstimulated saliva group was 5,32±0,304. The sample group that did not consume carbonated drinks had a mean saliva pH of 6.62±0.455. The Mann- Whitney test revealed a significant difference in pH between stimulated and unstimulated saliva after carbonated drinks (p=0.000; p<0.05). The conclusion is that carbonated drinks affect the pH of both stimulated and unstimulated saliva.